2003
DOI: 10.1002/ptr.1120
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of Propolis on hepatic injury and its mechanism

Abstract: Propolis (PP) is a sticky substance that is collected from plants by honeybees. The purpose of this study was to investigate the protective effects of PP on hepatotoxicity induced by acetaminophen (AA, paracetamol) and the mechanism of its hepatoprotective effect. In rat hepatocyte culture, pretreatment with PP (1, 10, 100, 200 and 400 microg/mL, 24 h) significantly decreased the cytotoxicity of AA (0.5 mm) in a dose-dependent manner. In mice, pretreatment with PP (10 and 25 mg/kg, p.o., 7 days) also decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This is in line with the findings of Zhang et al (2009) where immersion administration with 0.02-0.03 g l -1 propolis solution resulted in significant increased in plasma AST and ALT activities of rainbow trout. Previous studies demonstrated that quinic acid derivatives naturally present in propolis have strong liverprotective effects and promote healing of toxic liver cells (Seo et al 2003). …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Zhang et al (2009) where immersion administration with 0.02-0.03 g l -1 propolis solution resulted in significant increased in plasma AST and ALT activities of rainbow trout. Previous studies demonstrated that quinic acid derivatives naturally present in propolis have strong liverprotective effects and promote healing of toxic liver cells (Seo et al 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that the ethanolic extract of propolis has anti-inflammatory properties in both chronic and acute inflammation and exerts protective effects against hepatotoxicity (Seo et al 2003;Batista et al 2012). The molecular mechanisms involved in the immunomodulatory and antiinflammatory activities of this natural compound include the capacity of inhibiting T cell activation by affecting mainly IL-2, NF-κB, MAP, STAT 3, and IL-6 (Okamoto et al 2012;Búfalo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Propolis collected from different areas of the world has been reported to exert a protective effect against in vivo acute liver damage in rats treated with hepatotoxicants such as carbon tetrachloride [7–12], D-galactosamine [13, 14], acetaminophen [15, 16], and econazole [17] through its several pharmacological actions to suppress hepatic oxidative stress associated with lipid peroxidation [7–11, 13, 16, 17] to inhibit hepatic drug-metabolizing enzymes [11, 12, 14, 15] and to ameliorate hyperlipemia [7, 12]. However, it is still unknown whether propolis exerts a protective effect against in vivo acute liver damage with cholestasis in rats.…”
Section: Introductionmentioning
confidence: 99%